2011
DOI: 10.1016/j.respol.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on the determinants of essential patent claims in compatibility standards

Abstract: In the field of compatibility standards, an increasing number of companies claim to own so-called essential patents (i.e. those patents that are indispensable for designing and manufacturing products conforming to the standard). It is widely believed that the ownership of such patents is a very valuable bargaining tool in cross-license negotiations, while for non-producing firms such patents may result in a substantial stream of licensing revenues. In this paper we study the determinants of essential patent cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 29 publications
1
71
0
2
Order By: Relevance
“…This is a good proxy for the commercial value of the patent because the patenting company has to pay additional fees for each country in which it is registered (Bekkers et al, 2011).…”
Section: The Variablesmentioning
confidence: 99%
“…This is a good proxy for the commercial value of the patent because the patenting company has to pay additional fees for each country in which it is registered (Bekkers et al, 2011).…”
Section: The Variablesmentioning
confidence: 99%
“…By being part of such alliances and consortia, firms increase their chances of having their own (patented) technical contributions accepted in the standard. Bekkers et al (2011) studied the determinants of patents being (claimed) essential. They found that patents with a high value ('technical merit') have an increased likelihood of becoming (claimed) essential, but the patent owner being an active participant was a much better determinant.…”
Section: Features Of Sepsmentioning
confidence: 99%
“…Note that our set of selected patents does not include patents with a priority date older than 1999, the year in which the first of our 77 studied standardization meetings took place. This is important because earlier papers have observed that claimed essential patents preceding the standardization effort often have a much higher citation score, being selected for their technological contribution, even though they are 'old' (Bekkers et al, 2011). Excluding this group prevents unwanted bias in this respect.…”
Section: Testing the Third Hypothesis: Does The Technical Merit Of Jumentioning
confidence: 99%
“…Another important technology in the IMT-2000 family of technologies is TD-SCDMA, which is a standard developed in China. W-CDMA was most successful [53].…”
mentioning
confidence: 97%